Analysing post-earthquake landslide activity using multi-temporal landslide inventories near the epicentral area of the 2008 Wenchuan earthquake - Tang, Chenxiao (2020)
Large earthquakes in mountainous regions may trigger thousands of landslides, some active for years. We analysed the changes in landslide activity near the epicentre of the 2008 Wenchuan earthquake by generating five landslide inventories for different years through stereoscopic digital visual image interpretation. From May 2008 to April 2015, 660 new landslides occurred outside the coseismic landslide areas. In April 2015, the number of active landslides had gone down to 66, less than 1 % of the co-seismic landslides, but still much higher than the preearthquake levels. We expect that the landslide activity will continue to decay, but may be halted if extreme rainfall events occur.